Convection‐driven compaction as a possible origin of Enceladus's long wavelength topography. Issue 5 (6th May 2013) - Besserer, J.; Nimmo, F.; Roberts, J. H.; Pappalardo, R. T.
Abstract : [1] The long wavelength surface topography of Enceladus shows depressions about 1 km in depth and ∼10 2  km wide. One possible cause of this topography is spatially variable amounts of compaction of an initially porous ice shell, driven by spatial variations in heat flux. Here, we show that the heat flux variations associated with convection in the shell can quantitatively match the observed features. We develop a simple model of viscous compaction that includes the effect of porosity on thermal conductivity, and find that an initial shell porosity of at least 20–25% is required to develop the observed topography over ∼1 Ga. This mechanism produces topographic depressions, not rises, above convective upwellings, and does not generate detectable gravity anomalies. Unlike transient dynamic topography, it can potentially leave a permanent record of ancient convective processes in the shallow lithospheres of icy satellites. Key Points: pore compaction can explain the long wavelength topography of Enceladus topographic depressions (not rises) are produced above convective upwellings pore compaction can leave a permanent record on the surface of icy satellites